A Plasmonic Sensor Array with Ultrahigh Figures of Merit and Resonance Linewidths down to 3 nm. Issue 12 (6th February 2018) - Liu, Bowen; Chen, Shu; Zhang, Jiancheng; Yao, Xu; Zhong, Jinhui; Lin, Haixin; Huang, Tengxiang; Yang, Zhilin; Zhu, Jinfeng; Liu, Shou; Lienau, Christoph; Wang, Lei; et al.
Abstract: Surface plasmon polaritons (SPPs) are extremely sensitive to the surrounding refractive index and have found important applications in ultrasensitive label‐free sensing. Reducing the linewidth of an SPP mode is an effective way to improve the figure of merit (FOM) and hence the sensitivity of the plasmonic mode. Many efforts have been devoted to achieving a narrow linewidth by mode coupling, which inevitably results in an asymmetrical lineshape compromising the performance. Instead, the SPP modes are directly narrowed by elaborately engineering periodic plasmonic structures with minimized feature sizes to effectively reduce the radiative losses. A narrow linewidth smaller than 8 nm is achieved over a wide wavelength ranging from 600 to 960 nm and a minimum full width at half maximum of 3 nm at 960 nm. Benefiting from the almost perfect Lorentzian lineshape and the extremely narrow linewidth, a record FOM value of 730 is obtained. The sensor is capable of detecting bovine serum albumin with an ultralow concentration of 10 −10 m . The sensor has great potential for practical application for its ultrahigh FOM, broad working wavelength, and ease of high‐throughput fabrication. Abstract : A plasmonic array with linewidth down to 3 nm is reported, which benefits from the nearly completely suppressed metal losses. The array shows an ultrahigh sensitivity, with a record figure of merit of 730 for the bulk sensing. The array can work over a broad wavelength from 600 to 960 nm and can be fabricated with a low cost.